Abrasion Indicators for Smart Surfaces Based on a Luminescence Turn‐On Effect in Supraparticles - Wenderoth, Sarah; Granath, Tim; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl (Advanced Photonics Research, 2020)
Slight mechanical damage on surfaces or coatings caused, for example, by shear stress, is hardly detectable by simple means. Therefore, shear stress indicator particles for the creation of “interactive and communicating” coatings are presented. These are core-shell supraparticles obtained by a two-step spray-drying assembly process from nanoparticle dispersions. Three different types of nanoparticles are used to create the supraparticles: dye-doped silica nanoparticles responsible for the fluorescence signal, iron oxide nanoparticles acting as a fluorescence absorber, and pure silica nanoparticles regulating the indicator sensitivity. The creation of two different types of indicator systems is feasible by changing the nanoparticle arrangements within the supraparticle: A turn-off and a turn-on system, which indicate—after incorporation into a coating—shear stress by the decrease or the increase in the fluorescence intensity, respectively. Herein, two different mechanisms compete with each other: on the one hand, the change in the fluorescence signal due to physical light-absorbing effects, and on the other hand, the abrasion of luminescent material. The clear superiority of the turn-on system to achieve a reliable signal is demonstrated in this work. With the particle systems, interactive and communicating surface coatings are established.<br

Abrasion Indicators for Smart Surfaces Based on a Luminescence Turn‐On Effect in Supraparticles - Wenderoth, Sarah; Granath, Tim; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl (Advanced Photonics Research, 2020)
Slight mechanical damage on surfaces or coatings caused, for example, by shear stress, is hardly detectable by simple means. Therefore, shear stress indicator particles for the creation of “interactive and communicating” coatings are presented. These are core‐shell supraparticles obtained by a two‐step spray‐drying assembly process from nanoparticle dispersions. Three different types of nanoparticles are used to create the supraparticles: dye‐doped silica nanoparticles responsible for the fluorescence signal, iron oxide nanoparticles acting as a fluorescence absorber, and pure silica nanoparticles regulating the indicator sensitivity. The creation of two different types of indicator systems is feasible by changing the nanoparticle arrangements within the supraparticle: A turn‐off and a turn‐on system, which indicate—after incorporation into a coating—shear stress by the decrease or the increase in the fluorescence intensity, respectively. Herein, two different mechanisms compete with each other: on the one hand, the change in the fluorescence signal due to physical light‐absorbing effects, and on the other hand, the abrasion of luminescent material. The clear superiority of the turn‐on system to achieve a reliable signal is demonstrated in this work. With the particle systems, interactive and communicating surface coatings are established.<br
Keywords: abrasion indicators; communicating materials; smart surfaces; supraparticles; turn-on fluorescence

A code with a twist: Supraparticle microrod composites with direction dependent optical properties as anti-counterfeit labels - Wintzheimer, Susanne; Granath, Tim; Eppinger, Antonia; Goncalves, Manuel Rodrigues; Mandel, Karl (Nanoscale Advances, 2019)
Superparamagnetic iron oxide nanoparticles can be assembled to form anisotropic microrod supraparticles with the assistance of a magnetic field during synthesis. Optionally, these iron oxide microrods can furthermore be coated with a thin silica shell. Due to their anisotropic structure, both microrod types can be aligned in a magnetic field while being dispersed in a matrix material which can be cured during the alignment of the microrods. In this way, an anisotropic magnetic composite is obtained. Interestingly, it was observed that the optical extinction properties for visible light in such a composite are direction dependent, which can be explained by using appropriate models based on Maxwell equations. Based on the understanding of this principle, a clever approach for a hidden code could be proposed which is obtained from mixing pure iron oxide and silica coated microrod supraparticles in such an anisotropic composite. The hidden code, which comes down to obtaining a single value eventually, can only be revealed when knowing that the system needs to be measured with a certain "twist".
CRIS-Team Scopus Importer:2020-04-02

An all white magnet by combination of electronic properties of a white light emitting MOF with strong magnetic particle systems - Seuffert, Marcel T.; Wintzheimer, Susanne; Oppmann, Maximilian; Granath, Tim; Prieschl, Johannes; Alrefai, Anas; Holdt, Hans Jürgen; Müller-Buschbaum, Klaus; Mandel, Karl (Journal of Materials Chemistry C, 2020)
A multi-component particle system was developed that combines the properties of white color, white light emission and strong magnetism on the macroscopic and microscopic scale. The system is constituted by combination of an inorganic white core with either hard or soft magnetic properties and a white light emitting MOF. The key towards this achievement is the supraparticulate character constituted by a magnetic core, of either magnetite or α-Fe, surrounded by titania and silica nanoparticles of a certain size in a loose structural shell-arrangement as white components and finally the white light emitting metal-organic framework (MOF) EuTb@IFP-1 as building blocks of a core-shell structure. The supraparticles are created by forced assembly of the inorganic compounds and by combining spray-drying and postsynthetic modification by solvothermal chemistry. Thereby, the gap is bridged that homogenous compounds are either strongly magnetic, white in appearance or white light emitting. The composites presented herein inherit these properties intrinsically as electronic properties. The white characteristics are based on all optical properties that enable white: light reflection, refraction, and light emission. This work shifts the paradigm that strong magnetic materials are always expected to be intrinsically dark. This journal is
CRIS-Team Scopus Importer:2020-12-11

Anisotropic Magnetic Supraparticles with a Magnetic Particle Spectroscopy Fingerprint as Indicators for Cold-Chain Breach - Müssig, Stephan; Granath, Tim; Schembri, Tim; Fidler, Florian; Haddad, Daniel; Hiller, Karl-Heinz; Wintzheimer, Susanne; Mandel, Karl (ACS Applied Nano Materials, 2019)
Magnetic particle spectroscopy (MPS) is used in this work to obtain a magnetic fingerprint signal from anisotropic supraparticles, i.e., microrods assembled from superparamagnetic iron oxide nanoparticles. Exceeding its intended purpose of nanoparticle characterization for biomedical magnetic particle imaging, it is shown that MPS is capable of resolving structural differences between the anisotropic alignment of individual nanoparticles and its isotropic counterpart. Additionally, orientation-dependent MPS signal variations of anisotropic supraparticles are identifiable. This finding enables the detection of cold-chain breaches (for instance, during delivery of a product that needs to be cooled all of the time) by recording the initial and final MPS signals of microrod samples integrated into the container of a frozen product.
CRIS-Team Scopus Importer:2020-04-02
Keywords: cold-chain breach; detectors; magnetic particle spectroscopy; magnetic particles; magnetic sensor; supraparticles

Hollow Superparamagnetic Microballoons from Lifelike, Self-Directed Pickering Emulsions Based on Patchy Nanoparticles - Granath, Tim; Sanchez-Sanchez, Angela; Shmeliov, Aleksey; Nicolosi, Valeria; Fierro, Vanessa; Celzard, Alain; Mandel, Karl (ACS nano, 2016)
Herein, the formation of hollow microballoons derived from superparamagnetic iron oxide nanoparticles with silica patches is reported. Depending on the experimental conditions, single- or multishelled superparamagnetic microballoons as well as multivesicular structures were obtained. We show how such structural changes follow a lifelike process that is based on self-directing Pickering emulsions. We further demonstrate that the key toward the formation of such complex architectures is the patchy nature of the nanoparticles. Interestingly, no well-defined ordering of patches on the particles surface is required, unlike what theorists formerly predicted. The resultant hollow microballoons may be turned into hollow carbonaceous magnetic microspheres by simple pyrolysis. This opens the way to additional potential applications for such ultralightweight (density: 0.16 g·cm-3) materials.
CRIS-Team Scopus Importer:2020-04-02
Keywords: hollow particles; lifelike structures; microballoons; patchy nanoparticles; self-directed Pickering emulsions

Hollow Superparamagnetic Nanoparticle-Based Microballoons for Mechanical Force Monitoring by Magnetic Particle Spectroscopy - Wintzheimer, Susanne; Müssig, Stephan; Wenderoth, Sarah; Prieschl, Johannes; Granath, Tim; Fidler, Florian; Haddad, Daniel; Mandel, Karl (ACS Applied Nano Materials, 2019)
The determination of induced mechanical forces in ball mills is an ongoing problem, which is so far mainly addressed by simulations. Herein, we suggest utilizing superparamagnetic microballoons as sensor particles for mechanical stress. The defined assembly of superparamagnetic nanoparticles yields microballoons with hollow cores, which makes them susceptible to mechanical forces. It is shown that the hollow structure is continuously fragmented under static or dynamic force application. By use of magnetic particle spectroscopy, these structural changes are readily detected and enable the quantification of the applied mechanical forces in ball mills.
CRIS-Team Scopus Importer:2020-04-02
Keywords: ball milling; magnetic particle spectroscopy; magnetic particles; sensor; supraparticles

Luminescent magnets: hybrid supraparticles of a lanthanide-based MOF and ferromagnetic iron oxide by assembly in a droplet via spray-drying - Pujales Paradela, Rosa; Granath, Tim; Seuffert, Marcel T.; Kasper, Thomas; Mueller-Buschbaum, Klaus; Mandel, Karl (Journal of Materials Chemistry C, 2021)
Herein, we report on the successful creation of a luminescent micron-sized magnet. A spray-drying approach was employed to do "chemistry in a droplet" in order to achieve opto-magnetic hybrids in form of micron-scaled particles in a fast and easy way in a single step. This is possible by combining preformed nanoparticles, rare earth metal salts and organic precursors, ultimately leading to nucleation and crystallization of a crystalline lanthanide-based metal-organic framework (MOFs) entangled with the preformed ferromagnetic iron oxide nanoparticles (FIONs). Overall, a truly entangled and stable hybrid is obtained, which combines magnetic and optical properties simultaneously (luminescent magnet) and allows for a completely free choice of the ratios of the constituents and thus flexible and stepless property tuning. On the one hand, the material system that is exemplarily shown herein exhibits very interesting properties. On the other hand, the synthesis and assembly strategy serve as an example for various and more exotic property combinations that can easily be achieved and provides a new generation of truly tunable hybrids, which can be perfectly designed for use in many applications.
CRIS-Team WoS Importer:2021-12-31

Magnetic polyamide 11 powder for the powder bed fusion process by liquid-liquid phase separation and crystallization - Tischer, Florentin; Cholewa, Simon; Groppe, Philipp; Granath, Tim; Düsenberg, Björn; Mandel, Karl; Drummer, Dietmar; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2024)
Herein, we demonstrate the preparation of magnetic polyamide 11 feedstock powders for powder bed fusion (PBF) using liquid-liquid phase separation and crystallization. By adding magnetic nanomaterials during the precipitation process, the particulate additive is incorporated into the polymer matrix. This enables the production of filled systems at single particle level, which is advantageous in terms of the adjustable magnetic strength and homogeneity of the powder. Thermogravimetric analysis is used to determine the additive content and onset temperature of decomposition of composite powders, where additive-enhancement of PA11 powders with magnetic iron oxide nanoparticles showed a positive influence on the thermal stability of the feedstock. Successive analysis of particle size distribution, shape, colour, crystal structure, magnetic properties and thermal properties of the composite powders are carried out and their properties are discussed with respect to the PBF process. A decrease in particle size, width of the thermal process window and isothermal crystallization time can be attributed to the nucleating effect of the magnetic additive. The PBF processability of the composite feedstock is demonstrated by the production of magnetic tensile bar specimens from additive-enhanced PA11 powders with 1 wt.-% magnetic iron oxide.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Magnets; Nanocomposites; Polymer precipitation; Powder bed fusion; Powder characterization

Overcoming the Inhibition Effects of Citrate: Precipitation of Ferromagnetic Magnetite Nanoparticles with Tunable Morphology, Magnetic Properties, and Surface Charge via Ferrous Citrate Oxidation - Granath, Tim; Mandel, Karl; Loebmann, Peer (Particle & Particle Systems Characterization, 2021)
This study demonstrates how the method of thermally assisted oxidative precipitation in water can be opened for-the so far neglected-metal organic iron(II) complexes (herein: citrate) in order to obtain, in one step, ferromagnetic magnetite nanoparticles, possessing essential ligand properties. Based on a dedicated analysis of the specific precursor in combination with the consideration of known properties of the ligand, it is possible to identify existing inhibition-attributes of the iron organyl such that these can be overcome. Moreover, they can be exploited in a targeted manner; thus, simply by changing concentrations, a variety of magnetite nanoparticle morphologies with distinct properties can be obtained. In the case of the herein investigated ferrous citrate, three major inhibition effects are identified. While two of them efficiently prevent the formation of magnetite and need to be addressed to be overcome, the third can be exploited to selectively synthesize, for example, relatively stable carboxyl group-bearing nuclei clusters, exhibiting the properties of magnetically responsive photonic crystals, or relatively large mesocrystals, whose intraparticular magnetic interactions are apparently disturbed.
CRIS-Team WoS Importer:2021-07-09

Oxidative Precipitation as a Versatile Method to Obtain Ferromagnetic Fe3O4 Nano- and Mesocrystals Adjustable in Morphology and Magnetic Properties - Granath, Tim; Loebmann, Peer; Mandel, Karl (Particle & Particle Systems Characterization, 2021)
Oxidative precipitation is a facile synthesis method to obtain ferromagnetic iron oxide nanoparticles from ferrous salts-with unexplored potential. The concentration of base and oxidant alone strongly affects the particle's structure and thus their magnetic properties despite the same material, magnetite (Fe3O4), is obtained when precipitated with potassium hydroxide (KOH) from ferrous sulfate (FeSO4) and treated with potassium nitrate (KNO3) at appropriate temperature. Depending on the potassium hydroxide and potassium nitrate concentrations, it is possible to obtain a series of different types of either single crystals or mesocrystals. The time-dependent mesocrystal evolution can be revealed via electron microscopy and provides insights into the process of oriented attachment, yielding faceted particles, showing a facet-dependent reactivity. It is found that it is the nitrate and hydroxide concentration that influences the ligand exchange process and thus the crystallization pathways. The presence of sulfate ions contributes to the mesocrystal evolution as well, as sulfate apparently hinders further crystal fusion, as revealed via infrared spectroscopy. Finally, it is found that nitrite, as one possible and ecologically highly relevant reduction product occurring in nature in context with iron, only evolves if the reaction is quantitative.
CRIS-Team WoS Importer:2021-02-12

Pushing up the magnetisation values for iron oxide nanoparticles: Via zinc doping: X-ray studies on the particle's sub-nano structure of different synthesis routes - Szczerba, Wojciech; Zukrowski, Jan; Przybylski, Marek; Sikora, Marcin; Safonova, Olga; Shmeliov, Aleksey; Nicolosi, Valeria; Schneider, Michael; Granath, Tim; Oppmann, Maximilian; Strasser, Marion; Mandel, Karl (Physical Chemistry Chemical Physics, 2016)
The maximum magnetisation (saturation magnetisation) obtainable for iron oxide nanoparticles can be increased by doping the nanocrystals with non-magnetic elements such as zinc. Herein, we closely study how only slightly different synthesis approaches towards such doped nanoparticles strongly influence the resulting sub-nano/atomic structure. We compare two co-precipitation approaches, where we only vary the base (NaOH versus NH3), and a thermal decomposition route. These methods are the most commonly applied ones for synthesising doped iron oxide nanoparticles. The measurable magnetisation change upon zinc doping is about the same for all systems. However, the sub-nano structure, which we studied with Mössbauer and X-ray absorption near edge spectroscopy, differs tremendously. We found evidence that a much more complex picture has to be drawn regarding what happens upon Zn doping compared to what textbooks tell us about the mechanism. Our work demonstrates that it is crucial to study the obtained structures very precisely when "playing" with the atomic order in iron oxide nanocrystals.
CRIS-Team Scopus Importer:2020-04-02

Raspberry-like supraparticles from nanoparticle building-blocks as code-objects for hidden signatures readable by terahertz rays - Stumm, Christopher; Szielasko, Klaus; Granath, Tim; Stauch, Claudia; Mandel, Karl (Materials Today Communications, 2018)
Supraparticles, i.e., raspberry-like microparticles which are composed of nanoparticles (iron oxide), reveal specific interaction properties with terahertz (THz) rays. Depending on the density of the clustering of the nanoparticles within the raspberry-like supraparticle, characteristic THz components are altered upon transmission. The clustering can be adjusted upon supraparticle assembly via modification of the nanoparticles’ surfaces. By employing very densely and very loosely clustered supraparticles, a graphical coding system can be developed which allows creating signatures that are hidden in the bulk of a material (an object) and are easily and unambiguously decodable with THz rays.
CRIS-Team Scopus Importer:2020-04-02
Keywords: anti-counterfeit; codes; markers; supraparticles; terahertz

Smart Optical Composite Materials: Dispersions of Metal-Organic Framework@Superparamagnetic Microrods for Switchable Isotropic-Anisotropic Optical Properties - Mandel, Karl; Granath, Tim; Wehner, Tobias; Rey, Marcel; Stracke, Werner; Vogel, Nicolas; Sextl, Gerhard; Mueller-Buschbaum, Klaus (Acs Nano, 2017)
A smart optical composite material with dynamic isotropic and anisotropic optical properties by combination of luminescence and high reflectivity was developed. This combination enables switching between luminescence and angle-dependent reflectivity by changing the applied wavelength of light. The composite is formed as anisotropic core/shell particles by coating superparamagnetic iron oxide-silica microrods with a layer of the luminescent metal-organic framework (MOF) 3ınfty[Eu2(BDC)3]·2DMF·2H2O (BDC2- = 1,4-benzenedicarboxylate). The composite particles can be rotated by an external magnet. Their anisotropic shape causes changes in the reflectivity and diffraction of light depending on the orientation of the composite particle. These rotation-dependent optical properties are complemented by an isotropic luminescence resulting from the MOF shell. If illuminated by UV light, the particles exhibit isotropic luminescence while the same sample shows anisotropic optical properties when illuminated with visible light. In addition to direct switching, the optical properties can be tailored continuously between isotropic red emission and anisotropic reflection of light if the illuminating light is tuned through fractions of both UV and visible light. The integration and control of light emission modes within a homogeneous particle dispersion marks a smart optical material, addressing fundamental directions for research on switchable multifunctional materials. The material can function as an optic compass or could be used as an optic shutter that can be switched by a magnetic field, e.g., for an intensity control for waveguides in the visible range.
Keywords: anisotropy; composites; isotropy; magnetic actuation; metal organic frameworks; optical properties; smart materials; superparamagnetism; switching

Smart Surfaces: Magnetically Switchable Light Diffraction through Actuation of Superparamagnetic Plate-Like Microrods by Dynamic Magnetic Stray Field Landscapes - Koch, Iris; Granath, Tim; Hess, Sebastian; Ueltzhoeffer, Timo; Deumel, Sarah; Caballero, Claudia Itzel Jauregui; Ehresmann, Arno; Holzinger, Dennis; Mandel, Karl (Advanced Optical Materials, 2018)
This work reports on a remotely controllable, all-magnetic reflective diffraction grating-like optical element for electromagnetic waves in the visible spectrum. The switchable grating is realized by the unique interplay between nanostructured superparamagnetic plate-like microrods and a magnetic stray field landscape generated by an engineered magnetic stripe domain pattern superimposed by a small external magnetic field. It is shown that the purposeful design of local magnetic field sources in such a continuous thin-film system enables a precise manipulation of the microrod alignment and, hence, dynamic control of the corresponding grating constant. It is demonstrated that the magnetic grating can be turned on and off due to disappearance of the engineered domain pattern when magnetically saturated. Moreover, the grating constant can be dynamically changed between two states when applying an AC external magnetic field. The experimental findings are corroborated by a theoretical model based on a quantitative description of the involved forces among the microrods and between microrods and substrate, respectively. These results therefore serve as a basis for smart surfaces with switchable diffraction properties on demand upon remote control.
CRIS-Team Scopus Importer:2020-04-02
Keywords: exchange bias; ion-bombardment-induced magnetic patterning; magnetic field landscape; microrods; smart materials

Supraparticles: Functionality from Uniform Structural Motifs - Wintzheimer, Susanne; Granath, Tim; Oppmann, Maximilian; Kister, Thomas; Thai, Thibaut; Kraus, Tobias; Vogel, Nicolas; Mandel, Karl (ACS nano, 2018)
Under the right process conditions, nanoparticles can cluster together to form defined, dispersed structures, which can be termed supraparticles. Controlling the size, shape, and morphology of such entities is a central step in various fields of science and technology, ranging from colloid chemistry and soft matter physics to powder technology and pharmaceutical and food sciences. These diverse scientific communities have been investigating formation processes and structure/property relations of such supraparticles under completely different boundary conditions. On the fundamental side, the field is driven by the desire to gain maximum control of the assembly structures using very defined and tailored colloidal building blocks, whereas more applied disciplines focus on optimizing the functional properties from rather ill-defined starting materials. With this review article, we aim to provide a connecting perspective by outlining fundamental principles that govern the formation and functionality of supraparticles. We discuss the formation of supraparticles as a result of colloidal properties interplaying with external process parameters. We then outline how the structure of the supraparticles gives rise to diverse functional properties. They can be a result of the structure itself (emergent properties), of the colocalization of different, functional building blocks, or of coupling between individual particles in close proximity. Taken together, we aim to establish structure-property and process-structure relationships that provide unifying guidelines for the rational design of functional supraparticles with optimized properties. Finally, we aspire to connect the different disciplines by providing a categorized overview of the existing, diverging nomenclature of seemingly similar supraparticle structures.
CRIS-Team Scopus Importer:2020-04-02
Keywords: agglomeration; building blocks; colloids; complex particles; functionality; hierarchy; nanostructures; self-assembly; supraparticles

Surfactant free superparamagnetic iron oxide nanoparticles for stable ferrofluids in physiological solutions - Mandel, Karl; Strasser, M.; Granath, Tim; Dembski, S.; Sextl, G. (Chemical Communications, 2015)
A process is reported to obtain a nanoparticle sol from co-precipitated iron oxide particles without using any surfactant. The sol - a true ferrofluid - is not only stable over a wide range of pH but also in physiological solutions. This is a decisive step towards biomedical applications where nanoparticle agglomeration could so far only be prevented by using unwanted surfactants.
CRIS-Team Scopus Importer:2020-04-02

The Significant Influence of the pH Value on Citrate Coordination upon Modification of Superparamagnetic Iron Oxide Nanoparticles - Granath, Tim; Mandel, Karl; Loebmann, Peer (Particle & Particle Systems Characterization, 2022)
Although citrates are commonly used to modify nanoparticles, attention is rarely paid to how the modification parameters affect the type of adsorption and, thus, possibly, the properties of the modified particles. The relevance of this and the significant impact it can have is demonstrated in this study by examining the effect of pH upon the modification of superparamagnetic iron oxide nanoparticles (SPIONs) with citrate, using a citrate concentration that yields a high molecular surface density but induces almost no coordination pressure. Relying first on a number of classical surfaces analyzing methods, no clear pH-dependent differences can be identified. Finally, the consideration of the thermally induced redox behavior gives a decisive clue to unravel the "citric acid mystery" and to put together the, until then, weak hints into an overall picture. This shows that the citrate carboxyl groups are linked to the oxidic surface pH dependently via hydrogen bonds to hydroxide groups or coordinatively to iron ions and, besides, also interact, to a certain extent, with ammonia that is used for pH adjustment. With these findings, it is finally possible to explain the observed differences when the citrate-modified SPIONs are coated with silica (SiO2) or redispersed after spray-drying.
CRIS-Team WoS Importer:2022-02-11

Tuning Magnetic and Photophysical Properties of Luminomagnetic Metal-Organic Framework Composites in an Inverse Core-Satellite Structure - Seuffert, Marcel T.; Granath, Tim; Kasper, Thomas; Maile, Ruben; Pujales Paradela, Rosa; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl; Mueller-Buschbaum, Klaus (ChemPlusChem, 2022)
Luminomagnetic composites have been synthesized that allow for an individual tuning of luminescence intensity, chromaticity and magnetization by combination of superparamagnetic, citrate-stabilized iron oxide nanoparticles with the luminescent MOFs (3)(infinity)[Ln(2)(BDC)(3)(H2O)(4)] (Ln=Eu, Tb; BDC2-=terephthalate). The components are arranged to a concept of inverse structuring compared to previous luminomagnetic composites with MOF@magnetic particle (shell@core) composition so that the luminescent MOF now acts as core and is covered by magnetic nanoparticles forming the satellite shell. Thereby, the magnetic and photophysical properties are individually tuneable between high emission intensity (1.2 center dot 10(6) cps mg(-1)) plus low saturation magnetization (6 emu g(-1)) and the direct opposite (0.09 center dot 10(6) cps mg(-1); 42 emu g(-1)) by adjusting the particle coverage of the MOF. This is not achievable with a core-shell structure having a magnetic core and a dense MOF shell. The composition of the composites and the influence of different synthesis conditions on their properties were investigated by SEM/EDX, PXRD, magnetization measurements and photoluminescence spectroscopy.
CRIS-Team WoS Importer:2023-01-27